Encountering the Familiarity of a Foreign Culture: Julie Dash's Novel Daughters of the Dust - Gerund, Katharina (Current Objectives of Postgraduate American Studies, 2012)
This essay analyzes Julie Dash’s 1997 novel Daughters of the Dust “with regard to its portrayal of the Gullah culture, its strategies of familiarizing an outsider readership with a foreign culture, and the way it depicts representations of culture in anthropology and literature. The analysis works on two levels: it examines how intercultural encounters are portrayed in the novel as well as how the novel itself functions as “entry point“ to the Gullah culture. It argues that Dash presents cultures as distinct though not disclosed entities where boundaries can be transgressed though not transcended.